Health management 2.0 : transformational leadership for challenging times - Khan, Usman; Lega, Federico (European health management in transition, 2021)
From precision medicine to pandemics, from value-based healthcare to stakeholder engagement, European health systems are facing unprecedented change. How can health managers cope with these challenges and what skills and competencies will they need to deliver transformational change in the 'new normality'? This original volume presents a blueprint for Health Management 2.0 and helps set a path for long-term health system sustainability. Along with a comparative European framework to illustrate current developments in health management, the authors also highlight five key change drivers: integration; personalization; empowerment; digitalization; and life sciences, and examine how each is enabling the development of health systems that are fundamentally different from those of today. With fresh insights for managers, educators, researchers and policy makers, Health Management 2.0 promotes a modern interdisciplinary and dynamic approach to health leadership and management - one that focuses on skills and competencies - and outlines international best practice for future teaching and training.